(untitled) (Biological Sciences - PJSIR, 1999)
Chlorpromazine tetrabromopalladium (II), promethazine tetrabromopalladium (II), chlorpromazine tetraiodo palladium (II) and promethazine tetraiodopalladium (II) were prepared and characterized by IR, VIS spectra and elemental analysis. Asensitive,inexpensiveandrapidspectrophotometricmethodforthedeterminationofpalladium (II) hasbeen elaborated. The method allowsdeterminationof palladium (II)hasbeen elaborated. The method allows determination ofpalladium (II)intherangeof 10-100ug mol.Itwascheckedbythedetermination ofpalladium (II)in Degussa’s catalyst (E-207R).